A Review of the Antiviral Susceptibility of Human and Avian Influenza Viruses over the Last Decade - Ding Yuan Oh; Aeron C. Hurt (Scientifica)
Antivirals play an important role in the prevention and treatment of influenza infections, particularly in high-risk or severely ill patients. Two classes of influenza antivirals have been available in many countries over the last decade (2004–2013), the adamantanes and the neuraminidase inhibitors (NAIs). During this period, widespread adamantane resistance has developed in circulating influenza viruses rendering these drugs useless, resulting in the reliance on the most widely available NAI, oseltamivir. However, the emergence of oseltamivir-resistant seasonal A(H1N1) viruses in 2008 demonstrated that NAI-resistant viruses could also emerge and spread globally in a similar manner to that seen for adamantane-resistant viruses. Previously, it was believed that NAI-resistant viruses had compromised replication and/or transmission. Fortunately, in 2013, the majority of circulating human influenza viruses remain sensitive to all of the NAIs, but significant work by our laboratory and others is now underway to understand what enables NAI-resistant viruses to retain the capacity to replicate and transmit. In this review, we describe how the susceptibility of circulating human and avian influenza viruses has changed over the last ten years and describe some research studies that aim to understand how NAI-resistant human and avian influenza viruses may emerge in the future.